The way things work: Sound (Schlessinger Media, 2003)
The inhabitants of Mammoth Island learn how sound energy travels in waves, and one islander creates a primitive microphone, amplifier and loudspeaker.

Portable CD/cassette player (RCA)
Description Not Provided

Hide and seek sounds: Book 1,Attending to sound (Phonemic awareness, 1,, 2002)
Description Not Provided
Match sound to source , Match sequenced sounds to sources , Identify expected vs. real sound , Identify sounds in the environment , Identify nearby vs. faraway sounds , Follow three-part directions , Practice questions.

Headphone (V.ComMultiMedia Corp, 2000)
Description Not Provided

The complete guide to high-end audio (Acapella Pub, Acapella Publishing, 1998)
An updated edition of what many consider the "bible of high-end audio" In this newly revised and updated fifth edition, Robert Harley, editor in chief of the Absolute Sound magazine, tells you everything you need to know about buying and enjoying high-quality hi-fi. With this book, discover how to get the best sound for your money, how to identify the weak links in your system and upgrade where it will do the most good, how to set up and tweak your system for maximum performance, and how to become a more perceptive and appreciative listener. Just a few of the secrets you will learn cover high-end sound on a budget, how to do it cheap and still do it right; five system set-up mistakes and how to avoid them; how to make your speakers sound up to 50% better, at no cost; how to choose and set up a computer-based music system; how to find the one speaker in 50 worth owning; and why all 100-watt amplifiers don't sound the same. Since the first edition's publication in 1994, The Complete Guide to High-End Audio has been considered the essential reference on high-quality music reproduction, with more than 150,000 copies sold in five languages.

Audio visual source directory for services and products (Motion Picture Enterprises Publications)
Description Not Provided

Fundamentals of acoustics (Wiley, 1982)
Description Not Provided

Build your own home theater (Newnes, 2002)
Description Not Provided

The savvy guide to home theater (Indy-Tech Pub., (an imprint of Sams Technical Publishing, LLC), 2004)
Description Not Provided

The audiophile voice (Audiophile Society, 1991)
Description Not Provided

Guide to equipment for slide maintenance and viewing (Mid-America College Art Association of America, 1978)
Description Not Provided

Audio and video equipment basics for libraries (Music Library Association basic manual, no. 5,, 2006)
Description Not Provided
The listening environment , Source components , Video , Electronics , Sound producers , Miscellaneous.

Gaming headphone (V.ComMultiMedia Corp, 2000)
Description Not Provided

Headphones ([Audio-technica], 2018)
Description Not Provided

Record player ([producer not identified])
Description Not Provided

Waterproof bluetooth speaker (Comiso)
Description Not Provided

Megaphone (Pyle)
Description Not Provided

Karaoke machine (KaraoKing, 2019)
Get everything you need with the karaoke machine Bluetooth speaker. Includes two wireless microphones for kids and adults for double the delight. No need to connect the baby karaoke machine to a TV; it comes with a phone/tablet holder. With the remote control, this karaoke set has everything you need to put on the perfect party.

Portable speaker and mic ([producer not identified])
Description Not Provided

Portable CD player (HOTT Corp, 2019)
Description Not Provided